Are All Gay Men at Risk of Developing HIV/AIDS? Why China’s Mass HIV Testing Has Majorly Targeted Gay Men in the Era of Biomedicalization - Lei Yang; Zhipeng Sun (American Journal of Men's Health, 2024)
Global HIV/AIDS responses have been increasingly biomedically dominated over the past years. In line with this shifting paradigm, China has prioritized mass HIV testing as a practical approach to controlling its HIV/AIDS epidemics among at-risk populations, especially gay men and other men who have sex with men (MSM). This study analyzed why China’s mass HIV testing mainly targeted gay men by understanding the perspectives of public health professionals, community-based organization (CBO) workers, and gay men. In addition, this study revealed the tensions and unintended consequences of HIV/AIDS prevention and the representation of gay men in China. The study involved fieldwork conducted in a major city in Eastern China from 2015 to 2019. Semi-structured interviews were held with participants from the three abovementioned groups ( N = 25). The study identified four processes concerning why gay men are mainly targeted for HIV testing. Some public health professionals believe that being a gay man is equivalent to having HIV/AIDS risks. In addition, this study particularly noted tensions between public health professionals and gay men, including gay men–identified CBO workers, over whether mass HIV testing should target gay men or anyone who engaged in sexual risk behaviors. This study argued that a particular focus on gay men due to pursuing biomedical advances in HIV/AIDS prevention seems to have unintendedly stereotyped gay men based on the presumptions that they are at risk of developing HIV/AIDS. In addition, this study corresponded to the broader social scientific discussion concerning whether HIV/AIDS intervention should target specific sexual risk practices or sexual identity/population.